2021
DOI: 10.30658/icrcc.2021.14
|View full text |Cite
|
Sign up to set email alerts
|

Image Restoration Strategies for the (mis-) handling of COVID – 19 Pandemic in Greece

Abstract: During the COVID-19 pandemic outbreak all countries around the world used several kinds of response strategies to protect public health and control the outbreak. The main aim was to stop the disease from spreading into the community and put a pressure on the health system of the countries. However, severe measures like lockdown of cities and countries brought side-crises like economic pressure on the individuals, corporations and even the state itself. Although the Greek Government was considered to have manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Hotel managers may use the information from the current study to integrate crisis and strategic management practices to sustain their businesses [6]. Previous researchers concluded that managers need the ability and skills to deal with the aftermaths of natural disaster to sustain their business sustainability [7,8].…”
Section: ░ 1 Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Hotel managers may use the information from the current study to integrate crisis and strategic management practices to sustain their businesses [6]. Previous researchers concluded that managers need the ability and skills to deal with the aftermaths of natural disaster to sustain their business sustainability [7,8].…”
Section: ░ 1 Introductionmentioning
confidence: 93%
“…The proper use of image restoration strategies is to avoid the blame game [7]; therefore, it is important to point out that there is a lasting risk associated with perceived negative events regardless of the mitigating factors [15]. The theory of image restoration holds that communicators who need to restore damaged reputations have five strategic options: denial, evading responsibility, reducing offensiveness, corrective actions, and mortification [14], which provides organizational leaders with message strategies to sustain profits following a natural disaster such as a hurricane.…”
Section: ░ 3 Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations